State Bar Pro Bono Awards Reception-Costa Mesa - Watkins, Howard::::::::: (1983)
Howard Watkins and Hal Bolen holding State Bar Pro Bono Awards, Tomar Mason, Fresno County Bar Association President Doug Jensen